2020
DOI: 10.1002/adfm.202004276
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Trachea Regeneration Using a Modular Ring Strategy Based on Poly(Sebacoyl Diglyceride)/Polycaprolactone for Segmental Trachea Defect Repair

Abstract: The lack of a biomimetic tracheal substitute featured with cartilage ring/ vascularized connective tissue alternate structure (CVCAS) has significantly retarded a clinical breakthrough of tissue-engineered trachea in repairing extensive tracheal lesions. Herein, a novel modular strategy based on cartilage rings and biomaterial rings is used to generate a biomimetic trachea with CVCAS. Poly(sebacoyl diglyceride) and polycaprolactone (PCL) (PSeD/PCL) are blended to fabricate a porous scaffold with satisfactory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…The macro-morphologies of the prepared membranes were photographed using a digital camera and a digital vacuum scanning electron microscope (SEM, JEOL JSM-5600LV, Japan). Samples were critical-point dried and then examined using the SEM ( Xu et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The macro-morphologies of the prepared membranes were photographed using a digital camera and a digital vacuum scanning electron microscope (SEM, JEOL JSM-5600LV, Japan). Samples were critical-point dried and then examined using the SEM ( Xu et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…After 1 and 4 days of culture, the fibroblast viability on each membrane was evaluated using the Live and Dead Cell Viability Assay (Invitrogen, United States) following the manufacturer’s instructions, and the samples were examined using a confocal microscope (Nikon, Japan). The fibroblast viability was also measured using a cell counting kit-8 (CCK-8; Dojindo, Japan) following the manufacturer’s instructions, and the optical density (OD) was measured at 450 nm ( Xu et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Most literature recognizes the importance of tracheal lateral rigidity for normal respiration and ventilation, but they do not fully consider the tracheal longitudinal flexibility, which is needed to ensure the stability of the trachea during rotation, flexion, and extension of the neck ( Johnson et al, 2016 ; Xu et al, 2020a ). If a tracheal scaffold lacks the required longitudinal flexibility, the scaffold will become distorted, and the tracheal lumen will narrow during rotation, and the scaffold could tear during flexion and extension ( Xu et al, 2020b ). Hence, a new design mimicking the native tracheal anatomy could ensure the bionic function of a tracheal substitute ( Dikina et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Extensively studies have demonstrated that the pore size and three-dimensional structure of scaffolds are crucial factors for cell proliferation, differentiation, and ECM production during cartilage regeneration ( Shi et al, 2017 ; Chen et al, 2020a ; Li et al, 2020 ; Xu et al, 2020b ). Although it is generally accepted that ACM is a good scaffold material because of its biomimetic cartilage-specific microenvironment, it is difficult to prepare ACM as a three-dimensional structure with a tunable pore size owing to its poor crosslinking property ( Xu et al, 2017 ; Li et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%